Moving beyond targeted sanctions: The sanctions regime of the European Union against North Korea - Eric J. Ballbach (Stiftung Wissenschaft und Politik (SWP), 2022)
As diplomatic initiatives have thus far failed to achieve the objective of a complete, verifiable, and irreversible denuclearization of the Democratic People's Republic of Korea (DPRK), and given that a military solution is generally considered to be unfeasible, sanctions have become the central instrument of the international community in dealing with the threat from North Korea. While inherently linked to and built upon the respective resolutions of the UN Security Council, the EU's sanctions regime against North Korea succeeds the former in terms of quantity and quality, constituting the most comprehensive sanctions regime of the EU currently in operation. Since its inception in 2006, the EU's sanctions regime against the DPRK developed in several episodes, which are built upon different logics and objectives: coercion, constraining, signaling. The political explanation for the EU's decision to adopt autonomous sanctions results from a set of interrelated factors, most notably the general support for sanctions as an adequate tool for EU member states to use against North Korea, the influence of powerful member states, namely Germany, France, and (before Brexit) the UK, pushing for the imposition of autonomous EU measures, the lack of diplomatic engagement and economic interest, as well as third party pressure. While sanctions will remain an important aspect of the EU's North Korea strategy in the foreseeable future, it is in Brussels' interest to supplement its sanctions-based strategy with more proactive initiatives vis-à-vis North Korea, as the current approach has distinct negative strategic implications for the EU.
Keywords: 320